Ordinal Variables and the Measurement of Upward and Downward Intergenerational Mobility in European countries - Silber, Jacques (My University, 2020)
This article proposes a new approach to the measurement of intergenerational mobility in education. Using a “movement approach” to the measurement of mobility, it borrows the concept of inequality-sensitive and additive achievement measure that was recently introduced and axiomatically derived by Apouey et al. (forthcoming). Looking first at upward mobility, we define the extent of upward educational mobility for educational category i by focusing on fathers (or mothers) who are in category i and employing a weighted function of the proportion of their children who belong to category j, assuming that 𝑗≥𝑖. The paper then similarly defines the extent of downward educational mobility for the educational category i of the fathers (mothers) as a weighted function of the proportion of their children who belong to category 𝑗, assuming now that 𝑗≤𝑖. Total mobility is then defined as the fathers’ (mothers’) population weighted sum of the upward and downward mobility of the different educational categories i of the fathers (mothers), while net mobility is defined as the difference between the fathers’ (mothers’) population weighted difference between the upward and downward mobility of the different educational categories i of the fathers (mothers). The paper also presents an empirical illustration based on the 2016 European Social Survey that shows limited levels of total mobility in Central Europe, in contrast with particularly high levels in Nordic countries.
Keywords: Mobilidad-Europa; Education; intergenerational mobility; Europe; Inequality-sensitive and additive achievement